Understanding material shortage in Engineering-To-Order context: A case study - Månsson, Kristian; Abdi, Abdulahi Bashir (My University, 2025)
Material shortages are the leading cause of delivery delays in Engineering-To-Order (ETO) production at the studied Swedish automation company, affecting over 50% of late deliveries. This thesis identifies key internal factors, namely, unclear lead time ownership, poor coordination, inaccurate forecasting, and fragmented ERP data as the main contributors. To address this, a structured analysis model based on Fault Tree Analysis (FTA) is proposed. The model enables systematic root cause evaluation, helping distinguish between internal and external responsibility for shortages. It is intended to support proactive shortage prevention and foster a culture of accountability over reactive blame. The study is based on an abductive research approach, combining qualitative interviews (n=14) and quantitative analysis of ERP data from 2022–2025. Findings highlight the need for improved process visibility, clearer roles, and reliable data to support effective material planning in complex, customer-specific production environments.
Keywords: Engineering-To-Order (ETO), Material Shortage, Root Cause Analysis, Fault Tree Analysis, Supply Chain Management, ERP Systems